THERMAL POLYNOMIALS FOR THE INVERSE STEFAN PROBLEM - Касабек, Д. (Journal of Emerging Technologies and Computing, 2021)
The study of processes in the field of contact technology hasan important role all over the world. This article considers a mathematical modelof closed contact elements during heating. When an electrical contact is heated,many thermophysical processes occur. The Stefan problem is a mathematicalmodel of a process with a phase change, where heat is either absorbed orreleased. For example, the solidification of metals, the freezing of soil and water,the melting of ice, the growth of crystals, etc. There are two types of Stefan'sproblem, direct and inverse. In the first, the goal of the task is to find thetemperature distribution over the contact element and find the position of themovable boundaries. In the latter case, assuming that the moving boundaries areknown, we can create a heat flow function that determines the temperaturedistribution. This work gives an approximate solution by the method of heatpolynomials.